Truncated CPSF6 forms higher order complexes that bind and disrupt HIV-1 capsid - Ning, J; Zhong, Z; Fischer, D; Harris, G; Watkins, S; Ambrose, Z; Zhang, P (American Society for Microbiology, 2018)
Cleavage and polyadenylation specificity factor 6 (CPSF6) is a human protein that binds HIV-1 capsid and mediates nuclear transport and integration targeting of HIV-1 pre-integration complexes. Truncation of the protein at its C-terminal nuclear-targeting arginine/serine-rich (RS-) domain produces a protein, CPSF6-358, that potently inhibits HIV-1 infection by targeting the capsid and inhibiting nuclear entry. To understand the molecular mechanism behind this restriction, the interaction between CPSF6-358 and HIV-1 capsid was characterized using in vitro and in vivo assays. Purified CPSF6-358 protein formed oligomers and bound in vitro assembled wild-type (WT) capsid protein (CA) tubes but not CA tubes containing a mutation in the putative binding site of CPSF6. Intriguingly, binding of CPSF6-358 oligomers to WT CA tubes physically disrupted the tubular assemblies into small fragments. Further, fixed and live-cell imaging showed that stably expressed CPSF6-358 forms cytoplasmic punctae upon WT HIV-1 infection and leads to capsid permeabilization. These events did not occur when the HIV-1 capsid contained a mutation known to prevent CPSF6-binding nor did they occur in the presence of a small molecule inhibitor of capsid binding to CPSF6-358. Together, our in vitro biochemical and transmission electron microscopy data and in vivo intracellular imaging results provide the first direct evidence for an oligomeric nature of CPSF6-358 and suggest a plausible mechanism for restriction of HIV-1 infection by CPSF6-358.IMPORTANCE After entry into cells, the HIV-1 capsid, which contains the viral genome, interacts with numerous host cell factors to facilitate crucial events required for replication, including uncoating. One such host cell factor is called CPSF6, which is predominantly located in the cell nucleus and interacts with HIV-1 capsid. The interaction between CA and CPSF6 is critical during HIV-1 replication in vivo Truncation of CPSF6 leads to its localization to the cell cytoplasm and inhibition of HIV-1 infection. Here, we determined that truncated CPSF6 protein forms large higher order complexes that binds directly to HIV-1 capsid, leading to its disruption. Truncated CPSF6 expression in cell leads to premature capsid uncoating that is detrimental to HIV-1 infection. Our study provides the first direct evidence for an oligomeric nature of truncated CPSF6 and insights into the highly regulated process of HIV-1 capsid uncoating.